Expression and function of epithelial cell adhesion molecule EpCAM: where are we after 40 years? - Gires, Olivier; Pan, Min; Schinke, Henrik; Canis, Martin; Baeuerle, Patrick A. (Cancer and metastasis reviews, 2020)
EpCAM (epithelial cell adhesion molecule) was discovered four decades ago as a tumor antigen on colorectal carcinomas. Owing to its frequent and high expression on carcinomas and their metastases, EpCAM serves as a prognostic marker, a therapeutic target, and an anchor molecule on circulating and disseminated tumor cells (CTCs/DTCs), which are considered the major source for metastatic cancer cells. Today, EpCAM is reckoned as a multi-functional transmembrane protein involved in the regulation of cell adhesion, proliferation, migration, stemness, and epithelial-to-mesenchymal transition (EMT) of carcinoma cells. To fulfill these functions, EpCAM is instrumental in intra- and intercellular signaling as a full-length molecule and following regulated intramembrane proteolysis, generating functionally active extra- and intracellular fragments. Intact EpCAM and its proteolytic fragments interact with claudins, CD44, E-cadherin, epidermal growth factor receptor (EGFR), and intracellular signaling components of the WNT and Ras/Raf pathways, respectively. This plethora of functions contributes to shaping intratumor heterogeneity and partial EMT, which are major determinants of the clinical outcome of carcinoma patients. EpCAM represents a marker for the epithelial status of primary and systemic tumor cells and emerges as a measure for the metastatic capacity of CTCs. Consequentially, EpCAM has reclaimed potential as a prognostic marker and target on primary and systemic tumor cells.